Fine-Scale Mapping of the Nasonia Genome to Chromosomes Using a High-Density Genotyping Microarray - Desjardins, Christopher A. (Genetics Society of America, 2013)
Nasonia, a genus of four closely related parasitoid insect species, is a model system for genetic research. Their haplodiploid genetics (haploid males and diploid females) and interfertile species are advantageous for the genetic analysis of complex traits and the genetic basis of species differences. A fine-scale genomic map is an important tool for advancing genetic studies in this system. We developed and used a hybrid genotyping microarray to generate a high-resolution genetic map that covers 79% of the sequenced genome of Nasonia vitripennis. The microarray is based on differential hybridization of species-specific oligos between N. vitripennis and Nasonia giraulti at more than 20,000 markers spanning the Nasonia genome. The map places 729 scaffolds onto the five linkage groups of Nasonia, including locating many smaller scaffolds that would be difficult to map by other means. The microarray was used to characterize 26 segmental introgression lines containing chromosomal regions from one species in the genetic background of another. These segmental introgression lines have been used for rapid screening and mapping of quantitative trait loci involved in species differences. Finally, the microarray is extended to bulk-segregant analysis and genotyping of other Nasonia species combinations. These resources should further expand the usefulness of Nasonia for studies of the genetic basis and architecture of complex traits and speciation.